Overstatements in abstract conclusions claiming effectiveness of interventions in psychiatry: A meta-epidemiological investigation. - Kiyomi Shinohara; Aya M Suganuma; Hissei Imai; Nozomi Takeshima; Yu Hayasaka; Toshi A Furukawa (PLoS ONE, 2017)
Objective Abstracts of scientific reports are sometimes criticized for exaggerating significant results when compared to the corresponding full texts. Such abstracts can mislead the readers. We aimed to conduct a systematic review of overstatements in abstract conclusions in psychiatry trials. Methods We searched for randomized controlled trials published in 2014 that explicitly claimed effectiveness of any intervention for mental disorders in their abstract conclusion, using the Cochrane Register of Controlled Trials. Claims of effectiveness in abstract conclusion were categorized into three types: superiority (stating superiority of intervention to control), limited superiority (intervention has limited superiority), and equal efficactiveness (claiming equal effectiveness of intervention with standard treatment control), and full text results into three types: significant (all primary outcomes were statistically significant in favor of the intervention), mixed (primary outcomes included both significant and non-significant results), or all results non-significant. By comparing these classifications, we assessed whether each abstract was overstated. Our primary outcome was the proportion of overstated abstract conclusions. Results We identified and included 60 relevant trials. 20 out of 60 studies (33.3%) showed overstatements. Nine reports reported only significant results although none of their primary outcomes were significant. Large sample size (>300) and publication in high impact factor (IF>10) journals were associated with low occurrence of overstatements. Conclusions We found that one in three psychiatry studies claiming effectiveness in their abstract conclusion, either superior to control or equal to standard treatment, for any mental disorders were overstated in comparison with the full text results. Readers of the psychiatry literature are advised to scrutinize the full text results regardless of the claims in the abstract. Trial registration University hospital Medical Information Network (UMIN) Clinical Trials Registry (UMIN000018668).